The Implementation of Sharia Concepts in Surakarta Sharia Hotel to Products, Management and Services - Kurniawan, Fendy (Media Wisata, 2024)
The concept of sharia-based tourism is a concept that integrates sharia values into tourism activities by providing products, management and services that are in accordance with the provisions that apply in Islam (sharia). The research objective is how to apply the concept of sharia in the Surakarta Syariah Hotel. What are the obstacles in applying the sharia concept at the Surakarta Syariah Hotel. Based on the results of implementing the sharia concept in sharia hotels including products, management and services, they are still in the process of adjusting to the regulations that apply according to the provisions, basically these sharia-based hotels have a mechanism that refers to the Al-Quran and Hadith. This means that in offering its services, sharia hotels must prioritize halal both in the process and product results and implement sharia services. From several samples of sharia hotels in Surakarta, it turns out that there are still a number of hotels that do not have complete data, namely they do not yet have a halal certificate (in process) and have not fully implemented sharia kafah (fully). However, sharia-based hotels are a good start for development so that there is no sustainable disobedience in society. So that Muslim people who have a fairly good level of faith feel that the sharia hotel is in accordance with the provisions and concepts of sharia, because they can get a comfortable and blessed place to rest. The application of the sharia hotel concept in Surakarta that has been implemented is a process of integrating Islamic values into all aspects of activities and management in sharia hotels in Surakarta. The value of Islamic law as a belief and belief adhered to by Muslims is the basic reference in building hotel activities.